2023
DOI: 10.3389/fmicb.2022.1059549
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol and plant growth promotion potential of endophytic Bacillus subtilis JY-7-2L on Aconitum carmichaelii Debx.

Abstract: Aconitum carmichaelii Debx. is a famous medicinal plant rich in alkaloids and widely used to treat various human diseases in Asian countries. However, southern blight caused by Sclerotium rolfsii severely hampered the yield of A. carmichaelii. Beneficial microbe-based biological control is becoming a promising alternative and an environmentally friendly approach for the management of plant diseases. In this study, we evaluated the biocontrol potential of an endophytic bacterial strain JY-7-2L, which was isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Wu et al [ 99 ] have identified toluene, phenol, and benzothiazole as the main VOCs produced by B. amyloliquefaciens NJZJSB3, which have shown comparable effects to chemical fungicides in terms of reduction of canola stem rot incidence (by 83.3%), caused by Sclerotinia sclerotiorum, in pot experiments. Southern blight of Aconitum carmichaelii Debx., caused by Sclerotium rolfsii , was successfully inhibited (30% with a long-acting duration of up to 62 days) in a field trial by fermentation culture VOCs of B. subtilis JY-7-2L [ 100 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…Wu et al [ 99 ] have identified toluene, phenol, and benzothiazole as the main VOCs produced by B. amyloliquefaciens NJZJSB3, which have shown comparable effects to chemical fungicides in terms of reduction of canola stem rot incidence (by 83.3%), caused by Sclerotinia sclerotiorum, in pot experiments. Southern blight of Aconitum carmichaelii Debx., caused by Sclerotium rolfsii , was successfully inhibited (30% with a long-acting duration of up to 62 days) in a field trial by fermentation culture VOCs of B. subtilis JY-7-2L [ 100 ].…”
Section: Mechanisms Of Action Of Antifungal Bacillus ...mentioning
confidence: 99%
“…The dual-culture method was used to test the antifungal activity of endophytic bacteria both in vitro and on A. carmichaelii root slices. In this study, S. rolfsii and F. oxysporum strains were used as targeted pathogens (Li et al, 2020 ; Zou et al, 2023 ). Pathogens were inoculated on potato dextrose agar (PDA) medium and incubated at 25°C for 5 days.…”
Section: Methodsmentioning
confidence: 99%
“…SMR1 enhanced downy mildew tolerance in Papaver somniferum (L.) via protein modification, differential expression of transcripts related to signal transduction, transcription factors, and SA-dependent defense pathway ( Ray et al., 2021 ). Many researchers showed the ability of both bacterial and fungal endophytes to control diseases and phytopathogens by synthesized volatile and non-volatile compounds, soluble antifungal metabolites and by specific mechanisms including activation of defense enzymes and PR proteins associated with ISR, JA/ET mediated disease resistance, antagonism, antimicrobial, antioxidant, and anti-proliferative properties, production of IAA, siderophores.and β-1,3-glucanase, proteolytic activity, chitinase and cellulose synthesis in diverse medicinal plants including Chloranthus elatior , Taxillus chinensis, Salvia miltiorrhiza, Curcuma longa, Dioscorea bulbifera, Viola odorata, Cremastra appendiculata , Angelica sinensis , Cornus florida, Nicotiana tabacum, Zingiber zerumbet and Piper betle ( Harsha et al., 2023 ; Jiao et al., 2023 ; Manasa et al., 2023 ; Mei et al., 2023 ; Rotich and Mmbaga, 2023 ; Salwan et al., 2023 ; Santra and Banerjee, 2023 ; Sharma et al., 2023 ; Song et al., 2023 ; Thankam and Manuel, 2023 ; Wang et al., 2023 ; Yehia, 2023 ; Zou et al., 2023 ).…”
Section: Endophytes-mediated Plant-microbe Interactions To Mitigate E...mentioning
confidence: 99%
“…To illustrate, several studies have reported the beneficial effects of microbial endophytes on a wide range of medicinal plants, including Withania somnifera, Artemisia annua, Papaver somniferum, Cymbidium aloifolium , Salvia miltiorrhiza , Catharanthus roseus, Bacopa monnieri , Nicotiana tobaccum, Andrographis paniculata, Chlorophytum borivilianum, Panax ginseng, Panax notoginseng, Curcuma longa, Curcuma wenyujin , etc. ( Meng and He, 2011 ; Karthikeyan et al., 2012 ; Wang et al., 2012 ; Ma et al., 2013 ; Barnawal et al., 2016 ; Kumar et al., 2016 ; Hong et al., 2018 ; Jayakumar et al., 2019 ; Sahu et al., 2019 ; Shah et al., 2019 ; Jiao et al., 2020 ; Ray et al., 2021 ; Zheng et al., 2021 ; Mei et al., 2023 ; Salwan et al., 2023 ; Sharma et al., 2023 ; Song et al., 2023 ; Wang et al., 2023 ; Zou et al., 2023 ). Thus, unquestionably, these endophytes have demonstrated tremendous potential as a green and eco-friendly alternative for boosting food production in sustainable agricultural systems.…”
Section: Endophytic Microbes As Biostimulants In Sustainable Agriculturementioning
confidence: 99%